2022
DOI: 10.3389/fnbeh.2022.931549
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic consequences of early-life social isolation and chronic stress impact coping and neural mechanisms underlying male prairie vole susceptibility and resilience

Abstract: Chronic stress can be challenging, lead to maladaptive coping strategies, and cause negative mental and physical health outcomes. Early-life adversity exposes developing young to physical or psychological experiences that risks surpassing their capacity to effectively cope, thereby impacting their lifetime physical and mental wellbeing. Sensitivity to stressful events, like social isolation, has the potential to magnify stress-coping. Chronic stress through social defeat is an established paradigm that models … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 97 publications
(121 reference statements)
1
5
0
Order By: Relevance
“…2 ). These stress-induced outcomes complement what has been recently reported in adolescent male prairie voles (Sailer et al, 2022) – which display increases in time to approach a social target after a similar 10-day SDS protocol. Likewise, both female prairie and mandarin voles exhibit decreases in sociability after SDS exposure, however, additional depression-related phenotypes associated with helplessness, per increases in immobility in the forced swim and tail suspension tests, are observed only after chronic (14 episodes; Wang et al, 2019) and not acute SDS protocols (3 episodes; Tickerhoof et al, 2020).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…2 ). These stress-induced outcomes complement what has been recently reported in adolescent male prairie voles (Sailer et al, 2022) – which display increases in time to approach a social target after a similar 10-day SDS protocol. Likewise, both female prairie and mandarin voles exhibit decreases in sociability after SDS exposure, however, additional depression-related phenotypes associated with helplessness, per increases in immobility in the forced swim and tail suspension tests, are observed only after chronic (14 episodes; Wang et al, 2019) and not acute SDS protocols (3 episodes; Tickerhoof et al, 2020).…”
Section: Discussionsupporting
confidence: 82%
“…This finding is consistent with prior vole studies implementing chronic stress approaches resulting in reductions of sucrose preference after 4-weeks of social isolation (Grippo et al, 2008). Of note, previous work adopting acute stress protocols do not report anhedonia-like responses nor increases in corticosterone (Arai et al, 2016; Tickerhoof et al, 2020) – highlighting that chronic exposure to SDS is necessary to uncover anhedonia-like states, social withdrawal, and helplessness-related behavior in prairie voles (Sailer et al, 2022).…”
Section: Discussionmentioning
confidence: 89%
“…In contrast to work in mice and rats, most behaviors that we measured (USVs, non-aggressive behaviors, and huddling) were surprisingly not affected by short-term isolation. Similarly, Sailer et al (2022) found that juvenile prairie voles that experienced 9 days of social isolation engaged in social approach toward and social investigation of a conspecific behind a physical barrier at rates that were no different from animals that were not isolated. It is worth noting that combining social isolation while also exposing animals to a social stress regimen (i.e., chronic social defeat), however, reduced these behaviors [24].…”
Section: Discussionmentioning
confidence: 92%
“…In rodents, for example, social isolation increases levels of systemic inflammation and promotes anxiety-like and despair-like behaviors [21][22][23]. As in humans, social support in rodents buffers the effects of stressors, improves social investigation, and diminishes fear responses [14,15,24]. The consistent association between the quality (or absence) of social connections and psychophysiological health outcomes is a fundamental aspect of social animals across various taxa including primates, birds, fish, and invertebrates [20,25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation